2011
DOI: 10.3748/wjg.v17.i4.470
|View full text |Cite
|
Sign up to set email alerts
|

A potential oncogenic role of the commonly observed E2F5 overexpression in hepatocellular carcinoma

Abstract: To our knowledge, this is the first evidence that E2F5 is commonly overexpressed in primary HCC and that E2F5 knockdown significantly repressed the growth of HCC cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 19 publications
3
46
0
Order By: Relevance
“…The transcription factor E2F performs a central role in cell growth and proliferation by controlling cell cycle (26), which suggests that E2F5 may also be involved in cellular proliferation and cell cycle progression as an important member of the E2F family. Previous data has reported that E2F5 was overexpressed in various types of human cancer including breast, epithelial ovarian and prostate cancer and hepatocellular carcinoma, and closely associated with cancer progression and prognosis (16)(17)(18)(19). However, the role of E2F5 in GC remained unclear.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The transcription factor E2F performs a central role in cell growth and proliferation by controlling cell cycle (26), which suggests that E2F5 may also be involved in cellular proliferation and cell cycle progression as an important member of the E2F family. Previous data has reported that E2F5 was overexpressed in various types of human cancer including breast, epithelial ovarian and prostate cancer and hepatocellular carcinoma, and closely associated with cancer progression and prognosis (16)(17)(18)(19). However, the role of E2F5 in GC remained unclear.…”
Section: Discussionmentioning
confidence: 98%
“…As demonstrated in Fig. 3A, E2F transcription factor 5 protein (E2F5) was identified as an interesting candidate, as E2F5 has previously been observed as overexpressed in various types of cancer, including breast (16), epithelial ovarian (17), prostate cancer (18) and hepatocellular carcinoma (19), and is involved in cellular proliferation, cell growth and cell cycle progression. To investigate whether miRNA-34a is capable of regulating E2F5 expression in GC cells, qPCR was used.…”
Section: E2f5 Is a Direct Target Of Mirna-34amentioning
confidence: 99%
“…The present study implies that E2F5 as other E2Fs plays a vital role in apoptosis, senescence, proliferation, the DNA-damage response and DNA repair [11]. Jiang Y determined that E2F5 is commonly upregulated in HCC and that E2F5 knockdown significantly inhibits the growth of HCC cells [10]. However, the upstream mechanism that regulates E2F5 in HCC remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…E2F belongs to a family of transcription factors and was named for its function; E2F regulates transcription by binding to a common sequence (TTTSSCGC: S = C or G) known as an E2F site [9]. E2F5 is a member of the E2F family and regulates the expression of genes involved in cell cycle control by directly binding to the promoters of these genes [10]. The present study implies that E2F5 as other E2Fs plays a vital role in apoptosis, senescence, proliferation, the DNA-damage response and DNA repair [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dual-luciferase assay determined that E2F5 is a direct target of miR-154-5p. Amplification of the E2F5 gene has been frequently observed in various malignant tumors [5,6,11,12] . The DNA qPCR, Western blot analysis and immunohistochemical staining both found the significant higher expression of E2F5 proteins in PCa tissues than those in adjacent benign specimens, and the overexpression of E2F5 protein was significantly associated with a high Gleason score and an advanced clinical stage [7] .…”
Section: E2f5 Is a Direct Target Gene Of Mir-154-5pmentioning
confidence: 99%